1992
DOI: 10.1111/j.1476-5381.1992.tb13395.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium‐dependent increase in vascular sensitivity to phenylephrine in long‐term streptozotocin diabetic rat aorta

Abstract: 1 The effect of short-and long-term streptozotocin (STZ)-induced diabetes (12 and 52 weeks) on the vascular response to phenylephrine was examined in the isolated thoracic aorta with and without intact endothelium from diabetic, age matched control rats and diabetic rats treated with insulin. 2 Twelve weeks after induction of diabetes, aortae with intact endothelium demonstrated no changes either in sensitivity (defined as pD2) or contractility (defined as the maximal developed tension per aortic tissue wet we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
35
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 41 publications
8
35
1
Order By: Relevance
“…Another investigation of vascular 1988), isolated reactivity of both aortae and mesenteric arteries in chronic rfused kidneys experimental diabetes showed that the increased contractile response to noradrenaline was evident only in the untreated diabetics, whereas treatment with insulin completely prevented the increase (Macleod, 1985). Similar findings were reported in a long-term study of diabetes where the aortae from untreated diabetic rats showed an increased sensitivity to the agonist, phenylephrine, which was partially corrected in the insulintreated group (Chang & Stevens, 1992). In one study of resistance artery function, of similar experimental design to our study, evidence of enhanced contractility to noradrenaline was revealed in both untreated and insulin treated diabetic rats, and similarly, incubation with a nitric oxide synthase inhibitor (L-NAME) resulted in an increase in sensitivity to noradrenaline in the diabetic vessels (Taylor et al, 1994a).…”
Section: Discussionsupporting
confidence: 71%
“…Another investigation of vascular 1988), isolated reactivity of both aortae and mesenteric arteries in chronic rfused kidneys experimental diabetes showed that the increased contractile response to noradrenaline was evident only in the untreated diabetics, whereas treatment with insulin completely prevented the increase (Macleod, 1985). Similar findings were reported in a long-term study of diabetes where the aortae from untreated diabetic rats showed an increased sensitivity to the agonist, phenylephrine, which was partially corrected in the insulintreated group (Chang & Stevens, 1992). In one study of resistance artery function, of similar experimental design to our study, evidence of enhanced contractility to noradrenaline was revealed in both untreated and insulin treated diabetic rats, and similarly, incubation with a nitric oxide synthase inhibitor (L-NAME) resulted in an increase in sensitivity to noradrenaline in the diabetic vessels (Taylor et al, 1994a).…”
Section: Discussionsupporting
confidence: 71%
“…Although our study suggests that STZ diabetes is associated with increases in vasoconstrictor responses to both ET-1 and MTX, other studies have shown both decreased [9,15,17] and increased [10,13] vasoconstrictor and vasodilator responses to ET-1 and both decreased [7,11] and increased [8,12,14] vasoconstrictor responses to a 1 adrenergic stimulation in STZ rats. This interstudy variation could result from differences in the vascular bed studied, the severity and duration of hyperglycaemia and differences in experimental procedures for measuring vasoconstriction [1].…”
Section: Discussioncontrasting
confidence: 41%
“…Discrepancies in vivo may result from differences in the degree and duration of hyperglycaemia, the presence of diabetic complications, and possibly in the state of endothelial function in the model studied. It is possible that differences in endothelium derived relaxing factor (EDRF) production may contribute to these variations since its function declines in proportion to the duration of hyperglycaemia in STZ diabetes, and it is known to inhibit ET release [12,34]. Acetylcholine-evoked relaxation of aortic rings was intact in our study (data not shown), suggesting that EDRF production remained unaffected by STZ diabetes in this vascular smooth muscle preparation.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…The thoracic aorta was removed, dissected free of fat and connective tissue, and cut into transverse rings 5 mm in length. 18,19 The rings were gently rotated on a stainless steel rod to remove the endothelium (denuded aorta). The tissues were kept in an oxygenated (95% O 2 , 5% CO 2 ) solution of Krebs-Henseleit (KH) buffer (144 mM NaCl, 5.9 mM KCl, 1.6 mM CaCl 2 , 1.2 mM MgSO 4 , 1.2 mM KH 2 PO 4 , 25 mM NaHCO 3 , and 11.1 mM D-glucose).…”
Section: Contraction Responsementioning
confidence: 99%